Localization and restaging of carcinoma prostate by (68)Gallium prostate-specific membrane antigen positron emission tomography computed tomography in patients with biochemical recurrence - Seniaray, Nikhil (Indian J Urol, 2020)
INTRODUCTION: Radical prostatectomy (RP) and radical radiotherapy (RT) are well established primary curative options for localized prostate cancer. Despite technical improvements, prostate-specific antigen (PSA)-recurrence after RP and RT is a common clinical scenario. We aimed to assess the role of (68)Gallium ((68)Ga) prostate-specific membrane antigen positron emission tomography computed tomography (PSMA PET/CT) in patients with biochemical recurrence of prostate cancer after RP or RT for the detection and localization recurrent and metastatic disease. MATERIALS AND METHODS: We ambispectively (70 retrospective and 100 prospective) analyzed the data of men with biochemical recurrence post-RP and post-RT who were evaluated by (68)Ga PSMA PET/CT at our institute. We aimed to assess the relationship between serum PSA levels and the probability of having a positive scan in patients with recurrent prostate cancer. RESULTS: The study included 170 men, all had adenocarcinoma of the prostate, 124/170 had previous RP and 46/170 had prior RT. The median serum PSA in the RP group was 1.8 ng/ml and 5.2 ng/ml in the RT group. In the post-RP cohort, the detection rate of (68)Ga PSMA PET/CT was 39.3% for PSA 0.2 to <0.5 ng/ml, 47.3% for PSA 0.5 to <1 ng/ml, 68.4% for PSA 1 to <2 ng/ml and 93.1% for PSA ≥2 ng/ml. In the post-RT group, the detection rate was 88.8% for PSA 2 to <4 ng/ml and 100% for PSA ≥4 ng/ml. CONCLUSIONS: (68)Ga PSMA PET/CT provides a novel imaging modality for the detection of prostate cancer recurrence and metastases at low posttreatment PSA levels, which may help in directing appropriate salvage treatments.